2017
DOI: 10.1212/wnl.0000000000003912
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light as a biomarker for mild traumatic brain injury in contact sports

Abstract: The results from these 2 independent cohort studies suggest that serum NFL is a highly sensitive biomarker for concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
265
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 295 publications
(292 citation statements)
references
References 25 publications
23
265
3
1
Order By: Relevance
“…In our cohort, there were no other reported events as trauma episodes, stroke, anesthesia during surgery, or metabolic diseases that were supposed to be associated with sNfL increase. [33][34][35][36] However, we are not able to completely exclude such factors. In MS, sNfL peaks can indicate subclinical disease activity even when clinical parameters and cerebral MRI seem to be stable.…”
Section: Discussionmentioning
confidence: 82%
“…In our cohort, there were no other reported events as trauma episodes, stroke, anesthesia during surgery, or metabolic diseases that were supposed to be associated with sNfL increase. [33][34][35][36] However, we are not able to completely exclude such factors. In MS, sNfL peaks can indicate subclinical disease activity even when clinical parameters and cerebral MRI seem to be stable.…”
Section: Discussionmentioning
confidence: 82%
“…Of note, previous studies have investigated the abovementioned markers in TBI patients and found evidence for increases in NFL, 53, 54 GFAP ,55 and Tau 56 concentrations, as well as decreased MBP ,57 in cerebral spinal fluid and/or serum. While serum and CSF were not analyzed in this study, RmTBI did affect expression of these markers in brain tissue in a similar manner.…”
Section: Discussionmentioning
confidence: 94%
“…It is not clear if these rapid tau changes represent axonal injury or release of pre-existing interstitial fluid tau into the blood across an injured blood-brain barrier (the latter seems more likely from a pathophysiological standpoint). Serum NfL correlates strongly with CSF NfL, is increased in active professional fighters [82], in ice hockey players with postconcussive syndrome [83] and in retired fighters who have neurological symptoms [82]. The marker increases over time in American football athletes over the course of a season, suggesting that it may be sensitive to repetitive subconcussive head impacts [84].…”
Section: Fluid Biomarkersmentioning
confidence: 99%